Refusals strategies on facebook among primary school children / Narinder Kaur A/P Bakhtawar Singh - Narinder Kaur, Bakhtawar Singh (2013)
This study investigates refusal strategies on Facebook among primary school children. Based on a Discourse Completion Test (DCT) which has twelve situations, thirty school-going children aged between 11 and 12 years old were asked to construct refusals for the various situations given. For this study, a group of 30 students were asked to respond to the situations where refusals to requests, refusals to suggestions, refusals to invitations and refusals to offers were made. The study aims to explore the types of refusal strategies frequently used by primary school children and what strategies are most revealed in the response to refusals used in the situations given within different settings such as family, formal and social. The data were analyzed and categorized according to the refusal taxonomy by Beebe, Takahashi and Uliss-Weltz (1990). It is found that these primary school children employed more indirect strategies compared to the direct strategies. The high frequency in the use of indirect strategies demonstrates that the subjects were aware of the fact that the use of indirect strategies lessens the face-threatening effect of the speech act of refusals. In fact the indirect strategies, “statement of alternative” enjoyed the highest frequency in the family settings while the indirect strategies “excuse, reasons and explanation” enjoyed the highest frequency in the formal and social settings. Finally, the possible justifications behind the variations in the productions of refusals are discussed. Key words: speech act, refusals, family settings, formal setting, social settings